Correlation between the thickness of ceramic restorations and the choice of resin cement: Literature review (Research, Society and Development, 2024)
In order to achieve a successful rehabilitation treatment, several protocols must be followed, one of which is adhesive cementation. When the polymerization of the resin cement occurs incompletely, there will be damage to adhesion and the properties of the ceramic, as well as resulting in greater degradation of the cementation line. The aim of this literature review is to discuss the correlation between the thickness of the ceramic restoration, the degree of light irradiance through the piece and the physical properties of the cementation line, thus aiding in the choice of resin cement. PubMed, SciELO, Scopus and Web of Science databases, as well as gray literature, were used to search for articles. A total of 185 articles were identified, and after reading them and excluding duplicate articles, 19 articles were selected that actually portrayed the subject. Most of the studies found an inversely proportional relationship between the thickness of the ceramic restoration and the following parameters: translucency of the piece, degree of conversion and microhardness of the resin cement. Although there are some controversies and limitations to the studies in this literature review, it can be concluded that the physical properties of the cementation line are directly influenced by the thickness, composition and translucency of the ceramic piece, and all these properties should be taken into account when choosing the cementing agent, with a thickness of 1.2mm being a safe limit for the use of light-curing resin cements. Above this value, the use of dual polymerization systems is recommended, as well as prolonged and multidirectional photoactivation.